Quadratic assignment approach for optimization of examination scheduling - Ahmad Nazari, Mohd Rose; Zarina, Mohamad; Hasni, Hassan (Hikari Ltd., 2015)
The increase in student enrolment into institution of higher learning, and the great increase in flexibility in choice of courses has made examination scheduling very difficult to handle in the traditional scheduling system. This paper investigates a quadratic assignment approach in examination scheduling by presenting a quadratic assignment approach to eliminate or reduce the level of conflicts in the examination timetabling. The examination with the highest number of students will be prioritized across all faculty courses, followed by other criteria such as courses with the highest number of students from different faculties. A framework for optimizing and handling the conflicts at all constraint levels is proposed to solve the examination scheduling problem.